PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Departemen Social Outreach & Local Development (SLD) dan Community Relations (CR) PT.Freeport Indonesia) - TSENAWATME, ALEKS (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : This study entitled influence health and safety studies on the performance of the employees of the Department of Social Outreach and Local Development ( SLD ) and Community Relations ( CR ) PT Freeport Indonesia Personal safety is the protection of employees from injuries caused by accidents related to job . A safety risk aspects of the work environment that can lead to fire , fear of electricity , cuts, bruises , sprains , broken bones , organ damage , vision and hearing .The purpose of this study was to Knowing What Occupational Health and Safety effect on Employee Performance in Social Ministry Outreach & Local Development / Community Relations ( SLD / CR ) PT Freeport Indonesia . This study uses a descriptive analysis and a quantitative approach using simple linear regression analysis techniques aided by the SPSS program . . Variables examined in this study consists of two variables , namely : ( 1 ) . Safety and health influence of independent ( independent variables ) are symbolized by X and ( 2 ) the employee's performance as the dependent variable ( bound ) are symbolized by Y.In this study population were all employees of the Regional Office V Pawnshop Manado . Based on a simple regression analysis were done , it can be obtained regression equation is Y = 19.835 + 0.461 X. This indicates that the variable x the safety and health of employees have a significant effect on the performance of the Department of Social Outreach & Local Development / Community Relations ( SLD / CR ) PT Freeport Indonesia . Demonstrated a significant influence on the calculated F value = 12.089 . is significant because it means greater than F table = 4.00 . With a significance level of 0.001 which is much smaller than ( < 0.05 ) mean safety and health and a significant positive effect on employee performance .Keywords : Safety , Occupational Health , Employee Performance